Keeping the rhythm: the impact of circadian clock on the immune response to cancer - Aiello, Ignacio (2023)
The circadian clock, responsible for the regulation of physiological and behavioral functions in the body, has been found to play a significant role in the development of cancer. Studies have shown that circadian disruption due to atypical activity periods or shift work may lead to several types of cancer, including breast, prostate, and colorectal cancer. The development of cancer and its response to therapeutic protocols are strongly influenced by innate and adaptive immune systems. Indeed, the balance between the activation of inflammatory pathways and immunological tolerance is crucial for tumor development. Macrophages, which play a determinant role in the immune response to the tumor, can differentiate into pro-inflammatory (M1) or anti-inflammatory (M2) profiles depending on the signals they receive. In this work, we try to unveil how the circadian clock plays a significant part in the regulation of tumor immunity, focusing mainly on macrophages present in the tumor. Daily patterns in the presence and function of several leukocytes, including macrophages and dendritic cells, have been observed in the tumor context. In addition, the relation between the major profiles of macrophages, M1 and M2, is compromised under conditions that disrupt the circadian clock, favoring the immunological tolerance in the tumor microenvironment and, thus, helping the tumor to escape immune surveillance. On the other hand, the presence of the tumor itself affects the circadian system, which could initiate a vicious circle in which the circadian clock gets worse along with tumor progression, affecting the macrophages present in the tumor,among other leukocytes, favoring a more tolerogenic immunity within the tumor.